Demand and unmet need for modern contraception among mothers from a Pelotas Birth Cohort - Gbènankpon Mathias Houvèssou; Simone Farías-Antúnez; Andréa D. Bertoldi; Mariângela Freitas da Silveira (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To determine the total demand and unmet need for contraception with modern methods and their determinants among mothers participating in the 2015 Pelotas Birth Cohort. METHODS Data from the 48-month follow-up of mothers participating in the 2015 Pelotas Birth Cohort were analyzed. Only biological mothers (aged up to 49 years) of children belonging to the 2015 Birth Cohort and who answered the 48-month questionnaire were included in the study sample. Logistic regression and respective 95% confidence intervals were used to determine associated factors. RESULTS The study sample consisted of 3577 biological mothers. The prevalence of use of any contraceptive and of modern contraceptives was 86.0% (95%CI: 84.8-87.1) and 84.9% (95%CI: 83.7-86.1), respectively. The prevalence of unmet need for modern contraceptives was 10.7% (95%CI: 9.7-11.7), and the total demand for contraceptives was 95.6%. The factors associated with an unmet need for modern contraception were being over 34 years of age (OR = 0.6, 95%CI: 0.5-0.8), not having a husband or partner (OR = 1.9, 95%CI: 1.4-2.6), not being the head of the household (OR = 0.6, 95%CI: 0.4-0.9), having had three or more pregnancies (OR = 1.9, 95%CI: 1.3-2.6), and having had an abortion at least once after the birth of the child participating in the cohort (OR = 1.9, 95%CI: 1.0-3.6). CONCLUSIONS Despite the high prevalence of modern contraceptive use, one in ten women had an unmet need for modern contraception and was at risk of unplanned pregnancy.